Implementation of the Yanbu'a Method in Improving Students' Qur'an Reading Fluence - Rozi, Fathor; Hasanah, Siti Zekiyetul; Amma, Lailatul; Sholihah, Hikmatus (Lembaga Yasin AlSys, 2023)
Learning the science of tajwid is not an easy matter for students, especially if teachers only use lecture and memorization methods which make students increasingly bored so they have difficulty understanding and memorizing the material. This research aims to examine the Yanbu'a method used in Tajwid science lessons. The research approach used is descriptive qualitative case study type. The research location is at the Nurul Jadid Islamic boarding school, especially in the Az-Zainiyah area. The data collection techniques used are observation or observations and interviews. Meanwhile, the data analysis techniques used are data reduction, data presentation, and drawing conclusions. From this research, it is known that the application of the Yanbu'a method at the Nurul Jadid Islamic boarding school in the Az-Zainiyah region is in accordance with the planning formula and the realization of effective implementation. The benchmark for fluency in reading the Al-Qur'an for students is also considered good, which is divided into 3 aspects of success, namely that every student can understand and master the makhorijul letters which are required to be practiced for 1 year, the characteristics of the hijaiyah letters, and understand recitation well. The students are said to be fluent and fit to carry out the recitation of the Qur’an.